2008
DOI: 10.1111/j.1444-2906.2008.01602.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary taurine and lipid contents on conjugated bile acid composition and growth performance of juvenile Japanese flounderParalichthys olivaceus

Abstract: The effects of dietary taurine levels and lipid contents on the conjugated bile acid composition and growth performance of juvenile Japanese flounder Paralichthys olivaceus were investigated. Six types of diet (three different levels of taurine at two different levels of lipid) were fed to juveniles (average body weight, 0.04 g). Fishmeal that was washed with 70% ethanol to remove taurine was used as the sole protein source. Feeding experiments were carried out at 20°C for 6 weeks. At the end of the experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 22 publications
0
12
1
1
Order By: Relevance
“…Taurine is a conditionally essential nutrient that performs multifaceted roles in fish physiology. These roles include growth promotion (Lim et al, 2013), lipid digestion (Kim et al, 2008), antioxidant action (Han et al, 2014), neuroprotection (Lima et al, 2001) and detoxification (Hano et al, 2017). However, the biosynthetic capacity of taurine in many marine fish species is insufficient because the enzymes involved in its generation are either present at low levels or missing (Hano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Taurine is a conditionally essential nutrient that performs multifaceted roles in fish physiology. These roles include growth promotion (Lim et al, 2013), lipid digestion (Kim et al, 2008), antioxidant action (Han et al, 2014), neuroprotection (Lima et al, 2001) and detoxification (Hano et al, 2017). However, the biosynthetic capacity of taurine in many marine fish species is insufficient because the enzymes involved in its generation are either present at low levels or missing (Hano et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies proved that taurine is an essential nutrient for fish (Takagi et al 2008;Lim et al 2013; El-Sayed2014; Salze and Davis 2015) and involved in bile acid metabolism of fish (Goto et al 1996(Goto et al , 2017. Therefore, taurine enhances lipid metabolism of fish and improves the absorption of fat-soluble vitamins (Kim et al 2008;El-Sayed2014). A study conducted by Park et al (2002) indicated that dietary taurine was involved in a metabolism of sulfur amino acids of juvenile Japanese flounder (Paralichthys olivaceus).…”
Section: Introductionmentioning
confidence: 99%
“…As in mammals, taurine plays important roles in many physiological processes in fish including bile salt conjugation [ 18 ], osmoregulation [ 19 ], and vision [ 20 , 21 ]. In addition, dietary taurine supplementation has been shown to stimulate growth in multiple fish species, such as rainbow trout [ 22 ]; Japanese flounder [ 18 , 23 ]; turbot [ 24 ]; red seabream [ 25 , 26 ]; cobia [ 27 , 28 , 29 , 30 , 31 ]; Atlantic salmon [ 32 ]; and yellowtail [ 33 ].…”
Section: Introductionmentioning
confidence: 99%